Methodical approach to evaluation of intellectual potential of the enterprise - Зелінська, Г. О.; Зелінський, Р. Р. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
In the article the methodical approach to assessing the predictive potential of enterprises (IPP). Since there is currently no single vision in deciding assessment of intellectual potential of the company in the article are considered the most relevant approaches proposed by different researchers. Based on these approaches offered his own vision for the assessment of PPI, made ІРР the selection of indicators and their calculation algorithm. In applying the methodological approach company will be able to carry out an economic assessment of intellectual capacity that will provide him a competitive advantage in the market.